Integrating green initiatives into existing commerical buildings - Cheng, Yew Leong (2010)
The sustainable building movement is suffering a crisis of overhype and from focusing too often on new buildings. The refurbishment of existing buildings is a crucial yet often being neglected. Many old buildings waste large amounts of energy and provide poor internal conditions for occupants through poor lighting, poor ventilation, solar penetration and glare, and poor control of heating and cooling. Making existing buildings more sustainable will be the next big focus for the design industry. The aim of this research is to study the green concept applying to existing buildings; to establish the most critical of these aspects; and to identify methods to improve the existing buildings. The methodology for conducting the study involved literature review, data collection and analysis of results using the Average Index Method. The process of data collection involved obtaining primary data from the respondents by conducting questionnaires surveys and interview with building professional. The primary barriers and benefits towards green initiatives in existing building have been identified.